IMPLEMENTATION OF DATA ENCRYPTION STANDARD (DES) ALGORITHM FOR DATA SECURITY ON PDF DOCUMENTS - Panjaitan, Arif Wijaya; Zufria, Ilka; Nasution, Yusuf Ramadhan (ZERO: Jurnal Sains, Matematika dan Terapan, 2022)
Misuse and theft of confidential PDF documents because documents can still be recognized and read by humans means, of course, these problems can harm those who have access to PDF document data. The act of tapping and stealing PDF documents can be minimized by the application of cryptographic encryption techniques. Cryptography is a science that studies mathematical techniques related to information security aspects such as confidentiality, data integrity and authentication. Cryptography requires an algorithm to perform the encryption process, one of the cryptographic algorithms that can be used is the Standard Data Encryption (DES) algorithm. The DES algorithm is a symmetric algorithm that works on the principle of a block cipher. The DES algorithm uses a 64-bit key to encrypt a 64-bit block. This thesis discusses the design of web-based cryptography using the Data Encryption Standard (DES) method.The application of this system is hiding pdf files using an 8-bit key without any errors or file damage and cannot be decrypted without the appropriate key. By using a data security application system using the DES method, it is useful to help hide the contents of important pdf files with a key so as to minimize digital theft by irresponsible parties.